Short-term efficacy and safety of repaglinide versus glimepiride as augmentation of metformin in treating patients with type 2 diabetes mellitus - Xie J (Dove Medical Press, 2019)
Jing Xie,1 Ning Li,1 Xiaoyan Jiang,1 Liyin Chai,1 Jian-Jun Chen,2 Wuquan Deng11Department of Endocrinology and Nephrology, Chongqing University Central Hospital, Chongqing Emergency Medical Center, Chongqing 400014, People’s Republic of China; 2Institute of Life Sciences, Chongqing Medical University, Chongqing 400016, People’s Republic of ChinaBackground: Consistent evidence is still lacking on which one, glimepiride plus metformin or repaglinide plus metformin, is better in treating type 2 diabetes mellitus (T2DM). Therefore, this study was conducted to compare the short-term efficacy and safety of these two methods in treating T2DM.Methods: The literature research dating up to August 2018 was conducted in the electronic databases. The randomized controlled trials (RCTs) comparing the short-term (treatment period ≤12 weeks) efficacy and safety of these two methods in treating patients with T2DM were included. No language limitation was used in this study. The decreased hemoglobin A1c (HbA1c), fasting plasma glucose (FPG), and 2h plasma glucose (2hPG) levels were used as the primary outcome to assess the efficacy, and the adverse events and hypoglycemia were used as the secondary outcome to assess the safety.Results: In total, 11 RCTs composed of 844 T2DM patients were included. The results showed that there were no significant differences in decreasing HbA1c and FPG levels between the two methods, but the estimated standardized mean differences favored the repaglinide plus metformin. Meanwhile, the repaglinide plus metformin was significantly more effective in decreasing 2hPG levels than glimepiride plus metformin. In addition, fewer patients reported adverse events and experienced hypoglycemia in the repaglinide plus metformin group.Conclusion: These results indicated that the repaglinide plus metformin might have some advantages over glimepiride plus metformin in the short-term treatment of patients with T2DM, and should be further explored.Keywords: repaglinide, glimepiride, metformin, diabetes